Apatinib for Patients With Sorafenib-Refractory Advanced Hepatitis B Virus Related Hepatocellular Carcinoma: Results of a Pilot Study - Zhang, Yingqiang (Cancer Control, 2019)
More than half of the patients with advanced hepatocellular carcinoma (HCC) do not respond to primary treatment with sorafenib. Currently, there are no universally accepted methods for further treatment. This pilot study was performed to assess the safety and effectiveness of apatinib as an optional treatment for patients with sorafenib-refractory HCC. Between January 2015 and May 2017, 43 consecutive patients with sorafenib-refractory advanced HCC who received apatinib were reviewed. The objective response rate (ORR) and disease control rate (DCR) were assessed using modified response evaluation criteria in solid tumors. The time to progression (TTP) and overall survival (OS) were determined using the Kaplan-Meier method. Toxicities associated with apatinib were assessed. All patients had hepatitis B virus (HBV) related HCC. The mean follow-up time was 11 months (range: 3-37) and the mean duration of apatinib was 7.6 months (range: 1-32). After treatment, 11 patients had partial response (PR), 18 had stable disease (SD), and 14 had progressive disease (PD); accordingly, the ORR and DCR were 25.6% and 67.4%, respectively. The median TTP and OS were 3 months (95% confidence interval [CI]: 1.9-4.1) and 8 months (95% CI: 6.9-9.0), respectively. The median OS times for PR, SD, and PD were 19 months (95% CI: 15.8-22.2), 8 months (95% CI: 7.3-8.7), and 4 months (95% CI: 3.1-4.9), respectively (P < .001). The median TTP for PR, SD, and PD was 14 months (95% CI: 11.9-16.1), 3 months (95% CI: 2.3-3.7) and 1 month, respectively (P < .001). No patients experienced toxicity-related death. The most common toxicities were weight loss, hand–foot skin reaction, and hypertension. Twelve adverse events of grade 3 or higher were observed. Based on our findings, apatinib is a promising treatment for patients with sorafenib-refractory advanced HBV-related HCC.